Preemptive kidney transplantation: why, when, and how? - Moura,Ana Flávia (2022)
ABSTRACT Among renal replacement therapies, preemptive kidney transplantation (PKT) presents the best clinical, social, and economic results. However, it is still infrequently chosen as first therapy for patients with irreversible kidney failure. Initiatives in different parts of the world were developed to identify the reasons why PKT is still not widely used and to facilitate the access of patients with end-stage kidney disease to the advantages associated with it. This article addresses the main advantages and difficulties of PKT and discusses when it should be indicated and how to prepare potential recipients for PKT.